Eu voltei para reimplantar a tua memória: para os que não ouviram - Betella, Gabriela Kvacek [UNESP] (APESC - Associacao Pro-Ensino em Santa Cruz do Sul, 2014)
The oral records, deprived of great rhetoric elaboration, mark the family accounts and the testimonies about remarkable and apparently minor particularities of grand conflicts, like the World War II. The oral memory fulfilled an important function of historical transmission, especially in handing on to written record the organization of testimonies, revealing personal memories in the form of letters, diaries and narratives, besides of integrating itself to several works of fiction. In the present work we present the value of former partigiani’s testimonies collected in the volume Io sono l’ultimo (I am the last one) as evocation and transmission of personal remembrances strongly linked to the conflict and as manifestations in the literary field as well. The valuing by descendants and fellow countrymen of a tradition of memory communication make the testimony of men and women that fought for the liberation of many Italian locations much more than fragmented reports when the interested reader in the memory of those that survived, integrated to the micro-history of the events, perceive its expressive logic. We explore both the meaning of witness adopted by Giorgio Agamben and the esthetical value of the traumatized voice in the perspective of Márcio Seligman-Silva.

Os registros orais, desprovidos de grande elaboração retórica, marcam os relatos familiares e os depoimentos sobre episódios marcantes e particularidades aparentemente menores dos grandes conflitos, como a Segunda Guerra Mundial. A memória oral cumpriu uma importante função de transmissão da história, especialmente ao legar para o registro escrito a sistematização dos testemunhos, revelando memórias pessoais na forma de cartas, diários e narrativas, além de se incorporar a várias obras de ficção. Neste trabalho apresentamos o valor de testemunhos de ex-partigiani reunidos no volume Io sono l’ultimo (Eu sou o último) como evocação e transmissão de lembranças pessoais extremamente ligadas ao conflito e como manifestações no âmbito literário. A valorização de uma tradição de comunicação das lembranças pelos descendentes e pelos compatriotas torna o testemunho de homens e mulheres que lutaram pela libertação de muitas localidades italianas muito mais que relato fragmentado quando os leitores interessados na memória dos que sobreviveram, integrada à micro-história dos acontecimentos, percebem a sua lógica expressiva. Exploramos tanto o sentido de testemunha adotado por Giorgio Agamben, quanto o valor estético da voz traumatizada na perspectiva de Márcio Seligmann-Silva.
I came back to reimplant your memory: for those who did not hear
Keywords: World War II; Testimony; Representation; Io sono l’ultimo; Partigiani; Segunda Guerra Mundial; Testemunho; Representação; Io sono l’ultimo; Partigiani